2016
DOI: 10.1002/osp4.67
|View full text |Cite
|
Sign up to set email alerts
|

Electronically captured, patient‐reported physical function: an important vital sign in obesity medicine

Abstract: SummaryObjectivesImpaired physical function (i.e., inability to walk 200 feet, climb a flight of stairs or perform activities of daily living) predicts poor clinical outcomes and adversely impacts medical and surgical weight management. However, routine assessment physical function is seldom performed clinically. The PROMIS Physical Function Short Form 20a (SF‐20a) is a validated questionnaire for assessing patient reported physical function, which includes published T‐score percentiles adjusted for gender, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…1 4 5 6 Most patient-reported measurements used are not specifically designed to capture the health status of obese patients, and the literature lacks studies investigating the effect of obesity on the outcome of patient-reported measurements. 7 One such commonly used score is the Knee Injury and Osteoarthritis Outcome Score (KOOS). 8 KOOS is a standardized and validated instrument developed to evaluate knee and associated knee problems.…”
Section: Introductionmentioning
confidence: 99%
“…1 4 5 6 Most patient-reported measurements used are not specifically designed to capture the health status of obese patients, and the literature lacks studies investigating the effect of obesity on the outcome of patient-reported measurements. 7 One such commonly used score is the Knee Injury and Osteoarthritis Outcome Score (KOOS). 8 KOOS is a standardized and validated instrument developed to evaluate knee and associated knee problems.…”
Section: Introductionmentioning
confidence: 99%